The effect of hydrogen shielding gas on microstructure and abrasive wear behavior in the surface modification process using the tungsten inert gas method - Cay, V. V.; Ozan, S.; Gok, M. S. (Springer, 2011)
In this study, SAE 1020 steel surfaces were separately alloyed with preplaced high-carbon ferro-chromium (FeCr), ferro-molybdenum (FeMo), and ferro-titanium (FeTi) powders by using a tungsten inert gas (TIG) heat source. By using two different types of shielding gas compositions during the alloying process, the study investigated the effects of modified shielding gas composition on the microstructure, hardness, and abrasive wear resistance of specimens. It was observed that with modifications in shielding gas composition, the microstructure and volume hardness of the specimens changed and no cracks and voids were formed in the interface area. The X-ray examinations of the specimens identified Fe, FeTi, and FeMo phases in their microstructure as the first phase, and Cr7C3, Fe3C, Fe7C3, and TiC phases as the second phase. As a result, it was concluded that changes in shielding gas composition in surface alloying process significantly affect specimens' microstructure and mechanical properties.
Keywords: Coating; Shielding gas; TIG; Alloying; Microstructure